2022
DOI: 10.4236/jtts.2022.124034
|View full text |Cite
|
Sign up to set email alerts
|

Truck and Passenger Car Connected Vehicle Penetration on Indiana Roadways

Abstract: Commercially available connected vehicle (CV) probe data has been demonstrated to provide scalable and near-real-time methodologies to evaluate the performance of road networks for various applications. However, one of the major concerns of probe data for agencies is data sampling, particularly during low-volume overnight hours. This paper reports on an evaluation that looked at both connected passenger cars and connected trucks. This study analyzed 40 continuous count stations in Indiana that recorded more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Approximately 500 billion anonymized CV waypoint records for the month of December 2022 were aggregated into nearly 1 billion CV trip records for the entire United States. This data represents approximately 5% of the trips in the United States [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 500 billion anonymized CV waypoint records for the month of December 2022 were aggregated into nearly 1 billion CV trip records for the entire United States. This data represents approximately 5% of the trips in the United States [22].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging connected vehicle (CV) data can act as an alternative data source to potentially deliver a more scalable method to measure temporal and spatial usage of passenger vehicles in near real-time for a variety of applications, including trip origin-destinations, quantifying traffic congestion, travel mode choice, traffic safety, and infrastructure planning [16][17][18][19][20]. Early studies have shown that these CV datasets capture around 500 billion vehicle records in a month nationwide [21] for the United States, with a rough market penetration of 5-7% [22].…”
Section: Emerging Connected Vehicle Data Opportunitiesmentioning
confidence: 99%
“…Utah CV trajectory data provided by a third-party vehicle data vendor, with an estimated statewide MPR of 2.7% ( 37 ), is used. The data, obtained from passenger vehicles that were factory-equipped with the required technology, consists of vehicle trajectory waypoints with a 3-s reporting interval and 3.0 m of spatial accuracy.…”
Section: Data Descriptionmentioning
confidence: 99%
“…In this study, the available 2.7% MPR ( 37 ), aggregated over the analyzed five-day period, assuming CV data represents stochastic samples and similar traffic conditions, provides visibility equivalent to 13.5% of one day. This level of penetration is above the recommended values in the previous literature and is therefore assumed to provide accurate on-the-ground conditions ( 24 , 29 ).…”
Section: Data Descriptionmentioning
confidence: 99%
“…May and June 2022 Indiana CV trajectory data, with an estimated penetration rate of 4.5% ( 27 ), is used in this study. The data consists of individual passenger vehicle trajectory waypoints with a 3-s reporting interval and nominal 3-m spatial accuracy.…”
Section: Data Descriptionmentioning
confidence: 99%